Work ability, inclusion, and human resource development of disabled people - Futagami, Shiho; Kettunen, Erja; Jaussaud, Jacques (Taylor & Francis, 2026)
Our study focuses on the relationship between the work ability, inclusion, and human resource development of disabled people. It also explores the determinants and outcomes of their work ability and researches the benefits of an inclusive human resource management of disabled people. The study provides four main contributions on disability inclusion. Firstly, it compares the determinants of the work ability of disabled and non-disabled people by analysing a huge dataset. The results are indicative of the need for an inclusive human resource management of disabled people. Secondly, we focus on the inclusion perceived by disabled people themselves. The self-perceived improved inclusion of disabled people improves their work ability. Thirdly, we adopt an interdisciplinary approach to disability, which contributes in developing a comprehensive human resource development framework aimed at empowering individuals with disabilities. Finally, our study explores the relationship between the work ability, inclusion, and human resource development of disabled people, examining the determinants and outcomes of their work ability. The improved work ability of disabled people leads to their improved employability, paving the way for disability inclusion in the workplace.